CAPITAL MARKET REACTION TO PRABOWO-GIBRAN’S VICTORY IN THE 2024 PRESIDENTIAL ELECTION IN INDONESIA : TESTING ON INFOBANK15 - Fitriyani, Yuniar (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2024)
This research aims to analyze the capital market reaction to the event study of Prabowo-Gibran's victory in the Indonesian Presidential Election by comparing the variables of stock price, stock return and Infobank15 stock trading volume activity in the research period 20 days before and 20 days after the announcement on March 20 2024. Including quantitative research because the data taken is secondary data sourced from idx.co.id where the population which is also a sample is 15 leading banks with good performance according to the Indonesian Stock Exchange. The research results reveal that there is no difference in the average stock price, average stock return and average TVA before and after the announcement of Prabowo-Gibran's victory.